Wealth management: A Theravada Buddhist viewpoint - Kulatunga, S.T.K. (University of Colombo, Sri Lanka., 2019)
This paper examines the Theravada Buddhist views associated with wealth management. Using English translations by various authors of the Pali Canon, a qualitative content analysis is conducted using a sample of thirty (30) discourses of the Thripitaka which discusses wealth.
Keywords: accumulation, Buddhist economics, household, wealth, wealth management